2017
DOI: 10.3390/catal7070195
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Transfer of Pd Catalyst on Carbon–Carbon Triple Bond and Nitrogen–Nitrogen Double Bond in Suzuki–Miyaura Coupling Reaction

Abstract: Intramolecular transfer of t-Bu 3 P-ligated Pd catalyst on a carbon-carbon triple bond (C≡C) and nitrogen-nitrogen double bond (N=N) was investigated and compared with the case of a carbon-carbon double bond (C=C), which is resistant to intramolecular transfer of the Pd catalyst. Suzuki-Miyaura coupling reaction of equimolar 4,4'-dibromotolan (1a) or 4,4'-dibromoazobenzene (1b) with 3-isobutoxyphenylboronic acid (2) was carried out in the presence of t-Bu 3 P-ligated Pd precatalyst 3 and KOH/18-crown-6 as a ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The reaction of 1 e with 2 a in the presence of 3 afforded exclusively DP through intramolecular transfer of the Pd catalyst on 1 e (Entry 1), whereas MP would be the major product if the additive trapped the Pd catalyst during catalyst transfer on 1 e after the substitution of one of the two bromines in 1 e with 2 a . When styrene and stilbene, which disturbed intramolecular catalyst transfer on dibromostilbene [24] and dibromotolane, [25] were added, DP was almost the only product (Entries 2, 3); it turned out that these olefins cannot trap the Pd catalyst during catalyst transfer on the benzene ring, although they are effective as inhibitors of catalyst transfer on carbon‐carbon multiple bonds.…”
Section: Resultsmentioning
confidence: 99%
“…The reaction of 1 e with 2 a in the presence of 3 afforded exclusively DP through intramolecular transfer of the Pd catalyst on 1 e (Entry 1), whereas MP would be the major product if the additive trapped the Pd catalyst during catalyst transfer on 1 e after the substitution of one of the two bromines in 1 e with 2 a . When styrene and stilbene, which disturbed intramolecular catalyst transfer on dibromostilbene [24] and dibromotolane, [25] were added, DP was almost the only product (Entries 2, 3); it turned out that these olefins cannot trap the Pd catalyst during catalyst transfer on the benzene ring, although they are effective as inhibitors of catalyst transfer on carbon‐carbon multiple bonds.…”
Section: Resultsmentioning
confidence: 99%
“…We investigated catalyst transfer on not only aromatic rings, but also multiple bonds between benzene rings in the Suzuki–Miyaura coupling reaction. We found that t Bu 3 PPd moves on a carbon–carbon double bond (C=C) when alkoxy substituents are attached at the ortho ‐position of the benzene rings connected to C=C, and that intramolecular catalyst transfer takes place on a carbon–carbon triple bond and nitrogen–nitrogen double bond even when there are no substituents on the benzene rings . We had focused on catalyst transfer on π‐conjugated systems, and as an extension of that work, we were next interested in whether or not the Pd catalyst can undergo intramolecular catalyst transfer on functional groups located between benzene rings.…”
Section: Methodsmentioning
confidence: 99%
“…We found that tBu 3 PPd moves on a carbon-carbon doubleb ond (C=C) when alkoxy substituents are attached at the ortho-position of the benzene rings connected to C=C, [15] andt hat intramolecularc atalystt ransfer takes place on ac arbon-carbont riple bond and nitrogen-nitrogend ouble bond even when there are no substituents on the benzene rings. [16] We had focused on catalystt ransfer on p-conjugated systems, and as an extension of that work, we were next interested in whether or not the Pd catalystc an undergo intramolecular catalystt ransfer on functional groups located between benzene rings. If this is possible, CTCP could be extended to the synthesis of well-defined engineering plastics containing functionalg roups, such as keto and sulfonyl, as well as ether ands ulfide linkages.…”
mentioning
confidence: 99%
“…Most high-performing donor–acceptor polymers are synthesized in a step-growth manner from two difunctionalized monomers (e.g., a dihalide and a distannane) using tetrakis­(triphenyl)­phosphine palladium (Pd­(PPh 3 ) 4 ). , Similar to the infancy of palladium-catalyzed small-molecule cross-coupling, , Pd­(PPh 3 ) 4 is the workhorse precatalyst for conjugated polymers and is often used despite forming undesired (e.g., homocoupled) byproducts. In Pd-catalyzed small-molecule cross-coupling, however, significant developments in catalyst design have now enabled electron-deficient and -rich substrates with unprotected functional groups to be synthesized with few side products. While hundreds of ancillary ligands have been screened and optimized for these small-molecule cross-coupling reactions, comparatively few have been explored for synthesizing conjugated polymers, leaving a vast range of potential Pd precatalysts for CTP (Chart ) ,,, These ligands have been specifically optimized for Pd and, as such, will likely be more successful on Pd than on Ni for CTP . Herein, we highlight select examples of catalysts used in small-molecule cross-couplings as inspiration for expanding CTP.…”
Section: Why Palladium?mentioning
confidence: 99%